Hybridisation in Colias butterflies (Lepidoptera, Pieridae): identification of natural hybrids using unlinked molecular markers - Shapoval, Nazar A.; Krupitsky, Anatoly V.; Yakovlev, Roman V.; Kir'yanov, Alexander V.; Shapoval, Galina N. (Zenodo, 2023)
In this report, we analyze a wild-caught Colias specimen from Kyrgyzstan with unusual wing pattern, which was provisionally identified as a natural hybrid between Colias christophi helialaica Schulte, 1988 and Colias cocandica cocandica Erschoff, 1874 due to its intermediate phenotype. Using one mitochondrial ( COI barcode) and three nuclear ( Ca-ATPase , H3 and CAD gene fragments) markers, we confirm its hybrid origin and demonstrate that this specimen is a hybrid between a female of Colias christophi helialaica and a male of Colias cocandica cocandica . Our study shows that an analysis of mitochondrial and nuclear molecular markers can successfully discriminate natural hybrids in such a taxonomically challenging group of butterflies as the genus Colias . The authors are grateful to Alexander Baryshev (Penza, Russia) for providing material for DNA analysis. The study was supported by the grant of Russian Science Foundation grant No. 22-24-01086 (molecular analysis) and by the state research project No. 122031100272-3 (morphological analysis).